2020
DOI: 10.1089/scd.2020.0030
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells and their Extracellular Vesicle Progeny Decrease Injury in Poststenotic Swine Kidney Through Different Mechanisms

Abstract: Novel therapies are needed to address the increasing prevalence of chronic kidney disease. Mesenchymal stem/ stromal cells (MSCs) and MSC-derived extracellular vesicles (EVs) augment tissue repair. We tested the hypothesis that EVs are as effective as MSCs in protecting the stenotic kidney, but target different injury pathways. Pigs were studied after 16 weeks of renal injury achieved by diet-induced metabolic syndrome (MetS) and renal artery stenosis (RAS). Pigs were untreated or treated 4 weeks earlier with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…MetS is able to change the amount of loading of miRNA on EVs, upregulate ageing-related miRNA in EVs, and even limit the use of EVs in exogenous regenerative therapy through abnormal transcription [99][100][101]. Zhao et al found that autologous ADMSCs can better preserve microcirculation through comparative studies, while ADMSC-EVs perform better in retaining intactness of nephrocytes and reducing necrosis [102]. In summary, the application value of MSC-EVs in the treatment of ARVD remains in dispute, and further research is warranted to reveal their efficacy.…”
Section: Msc-evs and Atherosclerotic Renovascular Diseasesmentioning
confidence: 99%
“…MetS is able to change the amount of loading of miRNA on EVs, upregulate ageing-related miRNA in EVs, and even limit the use of EVs in exogenous regenerative therapy through abnormal transcription [99][100][101]. Zhao et al found that autologous ADMSCs can better preserve microcirculation through comparative studies, while ADMSC-EVs perform better in retaining intactness of nephrocytes and reducing necrosis [102]. In summary, the application value of MSC-EVs in the treatment of ARVD remains in dispute, and further research is warranted to reveal their efficacy.…”
Section: Msc-evs and Atherosclerotic Renovascular Diseasesmentioning
confidence: 99%
“…Besides, stem cells were shown to use paracrine pathways, for example, through microvesicles for transferring proteins and RNAs to endothelial cells 9 , 32 - 34 . In Lerman's study autologous endothelial and/or mesenchymal progenitor cells improved renal microvasculature via regulating growth factors Ang-1, VEGF and attenuated renal inflammation etc., which have direct meaning to stem cells' effect on nephrology 35 , 36 . Our study demonstrated that b-pEPCs promoted vascular tube formation and improved IR-induced vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, labeled EVs were detected in the stenotic kidney (9% of the injected amount) on day 2 after injection and decreased thereafter, remaining at 2% by four weeks after injection [103]. The same group reported a role for AD-MSC-derived EVs in preserving kidney cellular integrity after renal injury through their effect on necroptosis [114]. Consistently, exosomes derived from human AD-MSCs mitigated renal fibrosis in mice after unilateral renal I/R injury via activation of tubular Sox9 [105].…”
Section: Adipose Tissue Msc-derived Evs As Therapeutic Agents In Renamentioning
confidence: 90%